Identification with all humanity—A test of the factorial structure and measurement invariance of the scale in five countries. (8th June 2020) - Hamer, Katarzyna; Penczek, Marta; McFarland, Sam; Wlodarczyk, Anna; Łużniak‐Piecha, Magdalena; Golińska, Agnieszka; Cadena, Liliana Manrique; Ibarra, Manuel; Bertin, Paul; Delouvée, Sylvain
Abstract : Identification with all humanity measured as an individual characteristic is an important factor related to social and international relations, such as concern for global issues and human rights, prosocial attitudes, intergroup forgiveness, attitudes toward immigrants, solving global problems, reactions to hate crimes and dehumanisation. We examine the factorial structure, psychometric properties and measurement invariance of the Identification with All Humanity (IWAH) scale in student samples from five countries (the United States, Poland, France, Mexico and Chile; N = 1930). Separate confirmatory factor analyses (CFAs) for each country showed a second‐order model of one superordinate factor with two subfactors. The cross‐country validation of the scale, based on multigroup CFA, confirmed configural and metric invariance between countries for raw scores, and full metric invariance for "pure" scores. This study showed that the IWAH scale can be successfully used for cross‐country research and the results from different countries can be compared and integrated.